Perumusan Strategi Bersaing pada Grand Malabar Hotel - Ivan Godang Wardiman; Lukman Mohammad Baga; Popong Nurhayati (Value : Jurnal Manajemen dan Akuntansi, 2021)
The industry 4.0 revolution era, the hotel competitive rivalry competition, and the covid-19 pandemic are challenges for every industry to compete, especially the hospitality industry. Faced with this situation, a strategy is needed in winning the competition. This study is aimed to formulate a competitive strategy at the Grand Malabar Hotel in the midst of fierce competition in Bandung hospitality industry. This study uses primary and secondary data collected through observation, questionnaires, interviews, literature studies and related journals. This study combaines quantitative and qualitative approaches at the same time to optain optimal results. Importance-Performance Analysis (IPA) and Blue Ocean Strategy (BOS) are used as the methods of this study. The result of this study shows that currently the Grand Malabar Hotel is entering into red ocean. There are 13 competitive factors analyzed, 3 of which must be eliminated, 1 factor must be subtracted, and 7 factors must be increased. The nnovation has been made by creating 6 factors, including: (1) cooperation with travel agents, (2) creating hotel website, (3) information on tourist attractions, (4) utilization of IoT, (5) self service check-in kiosks, (6) rooftop cafe. The strategy formulation has been tested and commercially feasible to be implemented by Grand Malabar Hotel. Keywords: Blue ocean strategy (BOS), competitive strategy, hotel, importance-performance analysis (IPA), value innovation.